2002
DOI: 10.1177/147323000203000410
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Herbal Medicine Dai-Kenchu-to on Post-Operative Ileus

Abstract: Post-operative ileus (PI) is an inevitable

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 19 publications
0
81
0
Order By: Relevance
“…Dai-kenchu-to (DKT) is reported to be effective in treating uncomplicated postoperative intestinal obstruction (Ito et al, 2002;Ohya et al, 2003;Endo et al, 2006). It has been considered that DKT improves postoperative ileus by exerting gastroprokinetics effects on gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dai-kenchu-to (DKT) is reported to be effective in treating uncomplicated postoperative intestinal obstruction (Ito et al, 2002;Ohya et al, 2003;Endo et al, 2006). It has been considered that DKT improves postoperative ileus by exerting gastroprokinetics effects on gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…DKT is used conventionally for abdominal distention in Japan. It has been shown recently that DKT is useful for treatment of postoperative ileus, postoperative intestinal paralysis, irritable bowel syndrome and pediatric constipation (Ito et al, 2002;Ohya et al, 2003;Endo et al, 2006). DKT seems to improve postoperative quality of life (QOL) of patients after surgery for gastrointestinal disorders, since it makes possible for patients to shorten their duration of hospitalization (Endo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that DKT enhances GI motility both in vitro (7,8) and in vivo (6,9,10), as well as increasing intestinal blood flow (2, 11), reducing the blood ammonia level after hepatectomy (12), and exerting anti-inflammatory effects (13,14). Similarly, recent clinical studies have demonstrated that DKT improves not only GI motility after surgery (15,16) but also attenuates the progression of adhesional bowel obstruction due to abdominal surgery (17,18).…”
Section: Abstract Aim: Although It Has Been Widely Demonstrated Thatmentioning
confidence: 99%
“…Several studies have demonstrated that DKT enhances GI motility both in vitro (7,8) and in vivo (6, 9, 10), as well as increasing intestinal blood flow (2, 11), reducing the blood ammonia level after hepatectomy (12), and exerting anti-inflammatory effects (13,14). Similarly, recent clinical studies have demonstrated that DKT improves not only GI motility after surgery (15, 16) but also attenuates the progression of adhesional bowel obstruction due to abdominal surgery (17,18).Although several randomized controlled trials (RCTs) have confirmed the effects of DKT (19), previously demonstrated in animal models (13,20), for improving postoperative GI motility in patients undergoing abdominal surgery (21-25), few studies have investigated whether DKT reduces the occurrence of postoperative ileus (PI) in patients undergoing surgery for GI cancer as a primary end-point. Therefore, it seems reasonable to assume that, if DKT 5967…”
mentioning
confidence: 99%
“…We reported previously that intraluminal administration of DKT into the upper gut evoked phasic contractions at a locally administered site via cholinergic and 5-hydroxytryptamine 3 (5-HT 3 ) receptors in dogs (Shibata et al 1999a;Jin et al 2001). These observations were considered as the scientific support to the clinical effectiveness of DKT for uncomplicated adhesive bowel obstruction and postoperative ileus (Itoh et al 2002;Nakayama and Tanaka 2009). DKT also appears to be effective for morphine-induced constipation (Sato et al 2010b) and constipation in children (Iwai et al 2007) and in parkinsonian patients (Sakakibara et al 2005), suggest-ing that DKT may enhance motor activity of the colon.…”
Section: Introductionmentioning
confidence: 99%